Spalling prediction by distortion strain energy. Issue 1 (August 2021) - Alber, M; Bartmann, K
Abstract: Spalling can be a serious threat to underground excavation works in hard, good quality rock masses at great depth. Spalling endangers drill & blast advance or TBM drives with severe damage of tunnel walls or the face. In mining the concern is about spalling at pillars and at the face. Research on spalling is mainly associated with the definition of Crack Initiation (CI) and Crack Damage (CD) stresses and the definition of the S-shaped spalling strength envelope. Particularly CI stress at low confining stress (σc c/σ3 < 0.05 and σ1 /σ3 < 10) is important for defining spalling around an underground excavation in hard rock. We summarize 59 UCS tests and 197 triaxial tests (σ3 < 2.5 MPa) with sedimentary, magmatic, and metamorphic rocks, respectively, and defined robust CI and CD stresses. In this paper, we focus on the distortional strain energy at CI and CD stresses. From a rock mechanical point of view, crack initiation and crack damage are associated with stress (or strain) deviation. Analyses of the very well instrumented tests shows that for any rock type (saturated and dry) crack initiation (CI) occurs at 20% and crack damage (CD) at 75% of the distortion strain energy at failure. This approach was tested at the well-known case of spalling at the test tunnel in the AECL Underground Research Laboratory. Mechanical properties for the Lac du Bonnet granite were used to estimate distortional energy at CI and to model breakout depth and shape.